Comparative systematic review and meta-analysis of pregnancy outcomes after kidney transplantation - Bobotis, Stergios; Mavrommaths, Giorgos; Papalois, Vassilios (Frontiers in Transplantation, 2025)
IntroductionAdvancements in transplant medicine have increased the incidence of pregnancy among kidney transplant recipients. These pregnancies, however, carry elevated maternal and neonatal risks, warranting comprehensive outcome evaluation.Materials and methodsTo compare key maternal and neonatal outcomes in pregnancies following kidney transplantation with those in healthy pregnancies. A systematic search of MEDLINE, Embase, and PubMed was conducted up until December 2024. Comparative prospective and retrospective observational studies reporting maternal or neonatal outcomes in pregnancies among kidney transplant recipients and healthy controls. Risk of Bias in Non-Randomized Studies of Interventions (ROBINS-I) was used for quality assessment. Random-effects meta-analyses were conducted to calculate pooled odds ratios (ORs) with 95% confidence intervals (CIs) and heterogeneity (I2). Sensitivity analysis explored the impact of study design and bias.ResultsEight studies encompassing 893 pregnancies post-kidney transplantation were included. Relative to healthy pregnancies, kidney-transplant recipients showed markedly higher odds of pre-eclampsia (OR: 10.17, 95% CI: 4.25–24.35; I2 = 86%), gestational hypertension (OR: 7.40, 95% CI: 2.20–24.86; I2 = 84%) and preterm birth (OR: 13.65, 95% CI: 4.79–38.92; I2 = 96%). Caesarean delivery (OR: 3.95, 95% CI: 1.67–9.31; I2 = 93%) and fetal mortality (OR: 4.84, 95% CI: 1.33–17.57; I2 = 79%) were also higher, whereas gestational diabetes did not differ (OR: 1.06, 95% CI: 0.67–1.67; I2 = 0%). Sensitivity analyses confirmed the elevated risks of pre-eclampsia and preterm birth, whereas the associations with caesarean section and fetal mortality did not remain statistically significant after adjustment for study quality.ConclusionsPregnancies following kidney transplantation are associated with significantly increased maternal and neonatal risks. These findings underscore the need for specialized antenatal care and further large-scale prospective studies to optimize outcomes and inform clinical guidelines.